Degradation behaviour of arrowroot fibre (Maranta Arundinacea) Reinforced arrowroot starch biocomposite films - Tarique, J.; Sapuan, S. M.; Zainudin, E. S.; Khalina, A.; Ilyas, R. A. (Penerbit Akademia Baru, 2022)
This research is being driven by environmental legislation that requires the consumption and usage of environmentally friendly products. The focus of this research is to develop and characterize thermoplastic arrowroot starch (TPAS) based biocomposite films incorporating arrowroot fibre (AF) at various compositions (0–10 wt.%) using the solution casting method. The biodegradation behaviour of newly developed composite films was examined. The average degradation rates of TPAS and TPAS/AF–10 films were 8 and 9.84%/day, respectively. The soil burial results revealed that the weight loss of TPAS/AF biocomposite films was higher compared to TPAS film. The biocomposite films revealed arrowroot fibre, a novel waste resource that is both eco-friendly and simple to produce. Overall, incorporating arrowroot fibre with TPAS film improves biodegradability, making them more suitable for environmentally friendly food packaging.